Case report: Miliary tuberculosis complicated by pediatric acute respiratory distress syndrome in a 12-year-old girl - Zhu, Jiarui; Chen, Ning; Shang, Yunxiao; Feng, Yong (Frontiers in Pediatrics, 2023)
Acute respiratory distress syndrome (ARDS) is a rare complication of miliary tuberculosis, particularly in pediatric patients. Comorbidities and delayed diagnosis can worsen the prognosis of patients with miliary tuberculosis. A 12-year-old girl presented with fever for 20 days, and cough and tachypnea for 4 days. She was diagnosed with miliary tuberculosis complicated by pediatric ARDS. She had atypical clinical manifestations and imaging findings, a negative contact history, and negative results of a tuberculin skin test (TST) and T-SPOT.TB. Diagnostic bronchoscopy and bronchoalveolar lavage helped make the diagnosis of tuberculosis. Effective treatment was promptly initiated after confirmation of the diagnosis, and the patient’s condition improved. This case illustrates that a negative contact history and laboratory results cannot rule out tuberculosis. False-negative TST and T-SPOT.TB results should be evaluated carefully. Bronchoscopy may be useful for identifying pathogens in patients with pneumonia of unknown etiology, and corticosteroids should be administered with caution.